2014
DOI: 10.7314/apjcp.2014.15.7.3305
|View full text |Cite
|
Sign up to set email alerts
|

Physical Functions, Health-Related Outcomes, Nutritional Status, and Blood Markers in Community-Dwelling Cancer Survivors Aged 75 Years and Older

Abstract: Background: A cancer survivor is defined as anyone who has been diagnosed with cancer, from the time of diagnosis through the rest of their life. The purpose of this study was to examine whether physical functions, health-related outcomes, nutritional status and blood markers in community-dwelling cancer survivors aged 75 years and older are different from those who do not have cancer Materials and Methods: Two hundred seventy-five participants were asked by physicians, nurses, and physical therapists, questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 37 publications
(33 reference statements)
0
20
0
Order By: Relevance
“…Cheung et al 3 and Ihira et al 16 did not find an association between handgrip strength and cancer. However, Norman et al 6 showed that malnourished cancer patients had a lower handgrip strength.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Cheung et al 3 and Ihira et al 16 did not find an association between handgrip strength and cancer. However, Norman et al 6 showed that malnourished cancer patients had a lower handgrip strength.…”
Section: Discussionmentioning
confidence: 91%
“…Data were double entered in Statistical Package for the social Sciences (SPSS Inc., Chicago, Illinois, United States) 16.0 program and the analyses were performed using Stata (Stata Corporation, College Station, Texas, United States) 11.0 software. The analyses were weighted by poststratification weights to account for the sampling design.…”
Section: E T H O D Smentioning
confidence: 99%
“…The present prospective cohort study involved 411 community‐dwelling people aged ≥75 years enrolled in the project “Population‐based and Inspiring Potential Activity for Old‐old Inhabitants (PIPAOI)” from 2012 to 2013. This study was carried out in Bibai city (Japan), and the details of the PIPAOI project have been described previously . The inclusion criteria for the PIPAOI were being aged ≥75 years and residing in Bibai city (Japan).…”
Section: Methodsmentioning
confidence: 99%
“…Markers of nutritional status have been predictive of outcomes in gastrointestinal cancers (6)(7)(8). Specifically, body mass index (BMI) has been widely evaluated due to its ability to normalize for patient height (9)(10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%